Plant biochemistry - Heldt, Hans-Walter; Piechulla, Birgit (Elsevier ; Academic Press, 2011)
Presents the science on the molecular mechanisms of plant life. This book covers the basic principles of plant biology, such as photosynthesis, primary and secondary metabolism, the function of phytohormones, plant genetics, and plant biotechnology. It addresses the various commercial applications of plant biochemistry